Analysis of the reduction of tensile stress by post‐growth annealing methods in multicrystalline silicon wafers produced by the RST process. Issue 11 (30th September 2014) - Martínez, O.; Tejero, A.; Tupin, E.; González, M. A.; Jiménez, J.; Belouet, C.; Baillis, C.; Pizzini, Sergio; Kissinger, Gudrun
Abstract In this work, we analyze the residual stress, in both as‐grown and post‐growth annealed silicon ribbon on a sacrificial carbon template, by the simulation of the thermo‐mechanical behavior of the cooling ribbon using the Abaqus software, and the measurement of stress on the free silicon surface by µ‐Raman spectroscopy. The results of the simulations gave limits within which flat ribbons could be obtained for a combination of silicon thickness, ribbon width and pull rate. Stress relaxation by off‐line thermal treatments is used to optimize a post‐growth annealing furnace in line with the ribbon growth system. The fragile behavior of the ribbon during laser cutting can be considerably reduced by a short relaxation of the ribbon at medium temperatures around 850 °C, which were observed to give the best behavior in terms of residual tensile stress relaxation. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)